2020
DOI: 10.5194/hess-2020-450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Will UK peatland restoration reduce dissolved organic matter concentrations in upland drinking water supplies?

Abstract: Abstract. Rising dissolved organic matter (DOM) concentrations, and associated increases in water colour, have posed a potential problem for the UK water industry since the phenomenon was first reported in the early 1990s. Elevated DOM concentrations in raw water are of particular concern in upland catchments dominated by organic soils where DOM production tends to be highest. In recent years, water companies have considered the capacity for catchment interventions to improve raw water quality at source, relie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…On the other hand, other restoration activities have, in the short term, led to an increase of DOC (Qassim et al, 2015) or produced no difference (Alderson et al, 2019). A comprehensive review can be found in Williamson et al (2020), who conclude that restoration can increase the resilience of the system, bringing positive effects to the water sector, but alone it is not enough. Tools to monitor and predict the future DOC, are needed to make each intervention (whether it deals with the management of the catchment or it is an infrastructural operation) more targeted and well-timed.…”
Section: Implications For Water Security In Scotlandmentioning
confidence: 99%
“…On the other hand, other restoration activities have, in the short term, led to an increase of DOC (Qassim et al, 2015) or produced no difference (Alderson et al, 2019). A comprehensive review can be found in Williamson et al (2020), who conclude that restoration can increase the resilience of the system, bringing positive effects to the water sector, but alone it is not enough. Tools to monitor and predict the future DOC, are needed to make each intervention (whether it deals with the management of the catchment or it is an infrastructural operation) more targeted and well-timed.…”
Section: Implications For Water Security In Scotlandmentioning
confidence: 99%